Katabatic Wind‐Driven Exchange in Fjords. Issue 10 (28th October 2017) - Spall, Michael A.; Jackson, Rebecca H.; Straneo, Fiammetta
Abstract: The general issue of katabatic wind‐driven exchange in fjords is considered using an idealized numerical model, theory, and observations. Two regimes are identified. For fjords narrower than a viscous boundary layer width, the exchange is limited by a balance between wind and friction in lateral boundary layers. For the nonlinear viscous parameterization used here, this boundary layer thickness depends on the properties of the fjord, such as stratification and length, as well as on the wind stress and numerical parameters such as grid spacing and an empirical constant. For wider fjords typical of east Greenland, the balance is primarily between wind, the along‐fjord pressure gradient, and acceleration, in general agreement with previous two‐layer nonrotating theories. It is expected that O (10%) of the surface layer will be flushed out of the fjord by a single wind event. Application of the idealized model to a typical katabatic wind event produces outflowing velocities that are in general agreement with observations in Sermilik Fjord, a large glacial fjord in southeast Greenland. The presence of a sill has only a minor influence on the exchange until the sill penetrates over most of the lower layer thickness, in which cases the exchange is reduced. It is concluded that the multiple katabatic wind events per winter that are experienced by the fjords along east Greenland represent an important mechanism of exchange between the fjord and shelf, with implications for the renewal of warm, salty waters at depth and for the export of glacial freshwater in the upper layer. Plain Language Summary: Fjords represent an important connection between tidewater glaciers and the shelf ocean. Relatively warm waters from the ocean can melt the glaciers, leading to a loss of glacier mass and an introduction of fresh water to the ocean. We focus here on the influence of katabatic winds, events characterized by strong winds directed down the glacier towards the open ocean, on the exchange of water between the fjord and shelf. Theoretical considerations, computer models, and direct ocean observations in Sermilik Fjord along east Greenland support the conclusion that individual katabatic wind events can result in an exchange of approximately 10% of the fjord water mass. The multiple katabatic events that occur each year thus represent an important mechanism of exchange between the fjords of Greenland and the adjacent shelf. Key Points: Katabatic winds can force significant exchange between the fjords and shelf Friction limits exchange for narrow fjords Exchange in wide fjords is well predicted by two‐layer, nonrotating theory